Dementia: Formal Care, Assistance, and Caregivers. (11th November 2018) - Young, Y; Maher, B; Nakashima, T
Abstract: Introduction. The disease burden of dementia extends far beyond the healthcare and social needs of the person with dementia; its associated long-term care cost is prohibitive. To promote better care planning, this study aims to determine the diagnosis and care pathways for persons with dementia in the U.S. in comparison to Japan. Methods. Data was collected through semi-structured interviews of health professionals from various dementia care and service organizations (n=10). Qualitative analyses were performed to determine themes related to diagnosis and care pathways. Results. Similar to Japan, the U.S. has multiple access points to the diagnosis pathway. However, the U.S. diagnosis pathway often relies on entities that are not related to healthcare such as police officers, family members, neighbors, or adult protection services, while Japan has long-term care insurance with predetermined points of entry. Similar to the diagnosis pathway, the care pathway in the U.S. is more complex and is dictated by types of insurance plans and their coverage. Conclusion. Japan's diagnosis and care pathway has multiple access points, but each access point has a specific entity that coordinates it. Without national health insurance and universal long-term care coverage in the US, the navigation of the diagnosis and the care pathways is a daunting task. To promote early diagnosis and to reduce institutional care and related costs, a single point of entry, with professional assessment and case management that offer consumers one-stop access to information, support, and linkages to local care services, is essential.